Formation of 11-12-years-old children's relations in the process of physical training - Andriy Rostoka (Kazimierz Wielki University, 2017)
In the article peculiarities of interpersonal relations of children of average school age are determined under the influence of sports activities and physical training. Investigation results show that children, who actively go in for sports, are more decisive and ready for actions. They acknowledge leader's authority. In their activity and behavior they pay less attention to fathers and grandfathers' recommendations. Similarity in behavior of sportsmen children, both boys and girls, has been revealed. Such children are adapted to modern life.